PENGARUH KARAKTERISTIK PEKERJAAN DAN SELF EFIKASI TERHADAP KINERJA DENGAN MEDIASI KOMITMEN ORGANISASIONAL DAN KEPUASAN KERJA (STUDI PADA PEGAWAI DI PUSKESMAS EKS KAWEDANAN JUWANA - Sri Sadono, 12.4202.0024 (Jurnal Mahasiswa Pasca Sarjana, 2014)
Performance of employees in the Puskesmas is not optimal ex Kawedanan Juwana still are characterized by 9 coverage program that has not met the minimum service standards targets in Puskesmas. PHC services both inpatient and outpatient services in Pati not using Standard Operating Procedures (SOP). Puskesmas in Pati not do a customer satisfaction survey (Department of Health Pati, 2013). This study aims to determine the effect of job characteristics and self-efficacy on performance by mediating organizational commitment and job satisfaction (study on employee health center in Ex Kawedanan Juwana). The study population is 140. Purposive sampling technique that is taking the sample side with PNS criteria and service life of more than 4 years as many as 112 people. Test instrument using factor analysis, the validity test to look at the adequacy of the sample and test reliabiltas factor analysis to test the reliability of a measuring instrument with a Cronbach alpha look, model test with determination test and F-test, testing the hypothesis with multiple regression analysis. Results of the study note that the job characteristics and significant positive effect on organizational commitment . Self efficacy and significant positive effect on organizational commitment . Job characteristics and significant positive effect on job satisfaction . Self efficacy and significant positive effect on job satisfaction . Organizational commitment and a significant positive effect on job satisfaction . Self efficacy and significant positive effect on performance . Job characteristics and significant positive effect on performance . Job satisfaction is a positive and significant effect on performance . Organizational commitment and a significant positive effect on performance . The most dominant variable affecting the job satisfaction is organizational commitment , most dominant variables affect organizational commitment is self efficacy variable of the most dominant effect on performance is organizational commitment . Keywords : Job CharacteristicsÂ , self- efficacy , organizational commitment , job satisfaction and performance